Comparative performance analysis of Vacuum Insulation Panels in thermal window shutters. (January 2019) - Hashemi, Arman; Alam, Mahmood; Ip, Kenneth
Abstract: Windows are a major area of heat loss in buildings and can lose up to 10 times more energy than other building elements. In a typical house, around 10% of heat is lost through the windows. Thermal shutters could considerably reduce heat losses through windows and improve the energy performance of buildings. Insulation plays a major role in overall performance of thermal shutters. Advance insulation material such as Vacuum Insulation Panel (VIP) can help in improving the performance of thermal window shutters. VIP with a thermal conductivity of 0.005-0.008 W/mK is a high thermal resistance and energy efficient alternative to conventional thermal insulation materials. In this paper, effect of VIP and conventional insulation has been investigated and compared for enhancing the thermal performance of window shutters using computer simulations. Results indicate significant reduction in heat loss through windows when VIP insulation was employed in internal thermal window shutters. Thermal bridging was found to be the significant factor that deteriorated the performance of the shutter. Reducing heat loss through the frame and surrounding walls could improve the VIP insulated shutter thermal performance by approximately nine times.